2020
DOI: 10.3389/fcimb.2020.00323
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles: A Potential Biomarker for Quick Identification of Infectious Osteomyelitis

Abstract: Effective management of infectious osteomyelitis relies on timely microorganism identification and appropriate antibiotic therapy. Extracellular vesicles (EVs) carry protein and genetic information accumulated rapidly in the circulation upon infection. Rat osteomyelitis models infected by Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, and Escherichia coli were established for the present study. Serum EVs were isolated 3 days after infection. The size and number of serum EVs from inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…The EV-bacteria aggregates were characteristic for bacterial infections but were not present in non-infectious inflammation [ 131 ]. Similar results were reported in a rat osteomyelitis model and in patients with osteomyelitis, suggesting a selective aggregating ability of EVs with bacteria which were used to induce their production; however EVs showed some cross-reactivity with other bacteria as well [ 150 ]. It is also observed that alpha-2-macroglobulin positive EVs were present in higher amounts in survivors of pneumonia-related sepsis than non-survivors.…”
Section: Neutrophil-derived Evssupporting
confidence: 76%
See 1 more Smart Citation
“…The EV-bacteria aggregates were characteristic for bacterial infections but were not present in non-infectious inflammation [ 131 ]. Similar results were reported in a rat osteomyelitis model and in patients with osteomyelitis, suggesting a selective aggregating ability of EVs with bacteria which were used to induce their production; however EVs showed some cross-reactivity with other bacteria as well [ 150 ]. It is also observed that alpha-2-macroglobulin positive EVs were present in higher amounts in survivors of pneumonia-related sepsis than non-survivors.…”
Section: Neutrophil-derived Evssupporting
confidence: 76%
“…Although fMLP-induced PMN-EVs were able to bind bacteria via clusters of CR1 [ 110 ], no other receptor activation than Mac-1 resulted in antibacterial EV generation ( Figure 3 ) despite their ability to increase EV production related to spontaneous EV formation ( Figure 2 ). The aggregate forming ability of bacterial infection-induced PMN-EVs were later confirmed in septic patients [ 131 ] and in osteomyelitis patients [ 150 ]. Similar to bacteria-induced antibacterial EV formation, Shopova et al described antifungal PMN-EV release upon stimulation with opsonized A. fumigatus [ 122 ].…”
Section: Neutrophil-derived Evsmentioning
confidence: 99%
“…In addition to eukaryotic sRNA in exosomes, circulating sRNA (ASdes) from Mycobacterium tuberculosis was found in patients suffering from active tuberculosis, implicating their role as diagnostic biomarkers (Fu et al, 2018 ). This makes us hypothesize that some of the sRNAs we have validated in EVs (RNAIII and SsrA) have a potential to be used as biomarkers for bloodstream infections (Bordeau et al, 2016 ), joint infections (osteomyelitis) (Deng et al, 2020 ), tissues infections (e.g., chronic biofilm infections) and/or bacterial persistence (Romilly et al, 2014 ; Schoenfelder et al, 2019 ). Identifying sRNAs as biomarkers should not be limited to pathogenic strains but also to nasal and other commensal strains.…”
Section: Discussionmentioning
confidence: 99%
“…Organism-specific autoagglutinins eliciting visible autoaggregation can be utilized in disease diagnosis. Serum extracellular vesicles (EV) may mediate bacterial aggregation potentially specific enough to serve as a quick test to identify infection pathogens [ 71 ]. For example, serum-EVs from neutrophilic granulocytes/neutrophils isolated from osteomyelitis patients mediated aggregation of S. aureus ex vivo , albeit with weak cross-reaction with P. aeruginosa .…”
Section: Applications Of Autoaggregation Studiesmentioning
confidence: 99%